Mnemonic Value of Orthography for Vocabulary Learning in Monolinguals and Language Minority English-Speaking College Students. Issue 2 (5th July 2016) - Miles, Katharine Pace; Ehri, Linnea C.; Lauterbach, Mark D.
Abstract : The study examined whether exposure to spellings of new vocabulary words improved monolinguals' and language minority (LM) students' ( n  = 25) memory for pronunciations, meanings, and spellings of the words. College students who are native English-speaking monolinguals ( n  = 12) and LM students who learned English as their second language ( n  = 13) were taught the meanings of 20 words over five trials. During the trials, written forms of half the words were shown underneath the pictorial representation of the word. The participants were assessed on the pronunciation, meaning, and spelling of each word. Results indicated that including spellings improved memory for pronunciations and spellings of words but not for meaning. Additionally, monolinguals outperformed LM students on memory of pronunciations in both spelling conditions.